Development of Highly Stretchable Ag-MWCNT Composite for Screen-Printed Textile Electronics with Improved Mechanical and Electrical Properties - Janczak D; Wójkowska K; Raczyński T; Zych M; Lepak-Kuc S; Szałapak J; Nelo M; Kądziela A; Wróblewski G; Jantunen H; Jakubowska M (Nanotechnology, Science and Applications)
Daniel Janczak,1,2 Katarzyna Wójkowska,1 Tomasz Raczyński,1,2 Marcin Zych,2 Sandra Lepak-Kuc,1,2 Jerzy Szałapak,1,2 Mikko Nelo,3 Aleksandra Kądziela,1 Grzegorz Wróblewski,2 Heli Jantunen,3 Małgorzata Jakubowska1,2 1Institute of Mechanics and Printing, Faculty of Mechanical and Industrial Engineering, Warsaw University of Technology, Warsaw, Poland; 2The Centre for Advanced Materials and Technologies, Warsaw University of Technology, Warsaw, Poland; 3Microelectronics Research Unit, Faculty of Information Technology and Electrical Engineering, University of Oulu, Oulu, FinlandCorrespondence: Daniel Janczak, Institute of Mechanics and Printing, Faculty of Mechanical and Industrial Engineering, Warsaw University of Technology, 85 Narbutta Street, 02-524, Warsaw, Poland, Email daniel.janczak@pw.edu.plIntroduction: The rapid growth of flexible and wearable electronics has created a need for materials that offer both mechanical durability and high conductivity. Textile electronics, which integrate electronic pathways into fabrics, are pivotal in this field but face challenges in maintaining stable electrical performance under mechanical strain. This study develops highly stretchable silver multi-walled carbon nanotube (Ag-MWCNT) composites, tailored for screen printing and heat-transfer methods, to address these challenges.Methods: Silver flakes dispersed in a thermoplastic polyurethane (TPU) matrix formed the base composite, which was initially evaluated under tensile and cyclic stretching conditions. Resistance drift observed in these tests prompted the incorporation of multi-walled carbon nanotubes (MWCNTs). Leveraging their high aspect ratio and conductivity, MWCNTs were homogenized into the composite at varying concentrations. The resulting Ag-MWCNT composites were assessed through cyclic stretching and thermal shock tests to evaluate electrical and mechanical performance.Results: Incorporating MWCNTs improved composite performance, reducing resistance change amplitude by 40% and stabilizing resistance within 2– 8 Ohms under mechanical stress. These materials demonstrated superior electrical stability and durability, maintaining consistent performance over extended use compared to Ag/TPU alone.Discussion: This study highlights the critical role of MWCNTs in enhancing the reliability of conductive composites for textile electronics. By addressing resistance drift and stabilizing electrical properties, these advancements enable more robust and long-lasting wearable technologies. The demonstrated feasibility of combining screen-printing and heat-transfer techniques provides a scalable approach for manufacturing flexible electronics, paving the way for further innovation in industrial applications. Keywords: stretchable electronics, wearables, Ag-MWCNT composite, screen printing, textile electronics, IoT